2017
DOI: 10.1007/s00384-017-2832-6
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic predictors of participation in colorectal cancer screening

Abstract: Participation in colorectal cancer screening was high in Denmark in 2014 and 2015. Large differences in participation were seen between sociodemographic subgroups, potentially resulting in social inequality in the benefits from screening. Future efforts to increase participation should focus on the low compliance subgroups, such as singles, non-Western immigrants and people from the lowest socioeconomic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
39
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 15 publications
13
39
5
Order By: Relevance
“…In agreement with other studies, we found a lower participation rate among men and in the younger age group . It was in these groups which had low participation rates that the brief phone intervention had the greatest benefit.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with other studies, we found a lower participation rate among men and in the younger age group . It was in these groups which had low participation rates that the brief phone intervention had the greatest benefit.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with previous studies from Denmark and UK, we found that female gender was associated with increased participation in CRC screening [8,9]. Women's generally higher health-consciousness and preventive orientation might thus also manifest itself with respect to colon cancer screening.…”
Section: Sample Characteristicssupporting
confidence: 91%
“…For the overall study population, we identi ed a very high participation rate of 82,6%. The difference to the 65,3% participation rate reported by a Danish registry study for 2015/2016 [8] can be explained by the different criterion of "ever-use" (at least once) employed in the present study. What was con rmed was that in comparison to other countries [4], Danes in general have a high level of acceptance of the national colon cancer screening program.…”
Section: Sample Characteristicscontrasting
confidence: 83%
“…In the current study, ecological inference was used to confirm the non-randomness of spatial distributions (given by likelihood ratios) rather than to reconstruct individual associations from group-level data. Geographical distribution of colorectal cancer mortality and incidence in many world regions has been examined to date [25,26]. Colorectal cancer mortality was found to be higher in high-income countries [27], which is consistent with the interrelation between colorectal cancer mortality and salaries and wages observed in Poland (Tab.…”
Section: Discussionsupporting
confidence: 71%